2019
DOI: 10.7759/cureus.3992
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immunization Coverage in the Rural Area of Peshawar, Khyber Pakhtunkhwa

Abstract: Background: In children, the leading cause of morbidity and mortality is infectious disease. Immunization is one of the most cost-effective methods for child survival. The purpose of the survey is to assess access and coverage of immunizations in the rural areas of the District Peshawar, Khyber Pakhtunkhwa. Methods: A cross‑sectional study was conducted in a rural population area of District Peshawar from February 2016 to April 2016 using the WHO’s 30 cluster sampling method for evaluation of immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…Demographic, geopolitical, and religious concerns, which were more commonly cited in the literature, were often characterized in the literature as rumors about polio vaccination. Demographic concerns were focused on the potential fertility impacts of the polio vaccine on increasing sterility [27,31,35,36,[38][39][40][41]44,[47][48][49]. Closely related to demographic concerns were geopolitical anxieties about the true motive underlying the vaccine [26,40,44,49].…”
Section: Caregiver Beliefs Knowledge and Experiencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Demographic, geopolitical, and religious concerns, which were more commonly cited in the literature, were often characterized in the literature as rumors about polio vaccination. Demographic concerns were focused on the potential fertility impacts of the polio vaccine on increasing sterility [27,31,35,36,[38][39][40][41]44,[47][48][49]. Closely related to demographic concerns were geopolitical anxieties about the true motive underlying the vaccine [26,40,44,49].…”
Section: Caregiver Beliefs Knowledge and Experiencesmentioning
confidence: 99%
“…Limited knowledge of immunization schedules and the need for multiple polio vaccinations was highlighted by several studies as leading to incomplete polio vaccination [32,33,42,45,52,54]. Conversely, caregiver's awareness of the benefits of polio vaccination for their children was a strong facilitator of vaccination [32,35,42,47,48,56].…”
Section: Caregiver Beliefs Knowledge and Experiencesmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted in neighboring India reported somewhat similar statistics (prevalence of migraine among medical students 14%) (9). However some other studies reported a comparatively higher prevalence of migraine among this population group of South East Asian region such as 30% in India (10), 38% in Pakistan (11), and 35% in Nepal (12). In the studies conducted in different countries like Brazil (12%) (34), Nigeria (14%) (35), Turkey (13%) (36), and Oman (12%) reported slightly lower prevalence of migraine compared to .…”
Section: Discussionmentioning
confidence: 84%